Trashumancia, Espacio para Poesía y Arte : diciembre 92 - Ocaranza, Jorge Octavio (dirección); Gutiérrez Ramírez, Alfredo (edición) (Trashumancia, 1992)
Contiene obra de: Antonio López Mijares, Roberto Girri, Silvia Eugenia Castillero, Ricardo Chávez Castañeda, Andrés Costa, Citlali Ferrer, Ignacio Padilla, Jorge Amézquita Sahagún, Luis Ocaranza, Ted Hughes, David Huerta, Victor Manuel Pazarín, Giuseppe Ungaretti, Ana Aridjis, Félix Juan Martínez Rico, Grady Miller, Jorge Fernández Granados, José Carrillo, José de Jesús de Loza, Lourdes C. Pacheco Ladrón de Guevara, Margarita Valdivia, Mauricio Ramírez, Oryana Jáuregui y Salvador Encarnación.